Navigating Linguistic Landscape: Understanding Students Engagement in English Language Learning Within An Pesantren Setting - Hidayati, Dewi Syaroh; Elga Romadhon, M Galuh; Mustofa, Mutmainnah (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
This research aims to explore the level of student engagement in English language learning (ELL) in an Islamic boarding school, utilizing a phenomenological research methodology. The study's primary objectives are: firstly, to understand how students subjectively interpret and experience their engagement in ELL activities within the boarding school setting; secondly to analyze the contextual factors present in the Islamic school environment that students believe impact their engagement; and finally, to examine how students perceive the harmony or potential discord between the teaching and learning of English and their religious and cultural beliefs. The results of the study have been divided into three main themes: students' perspectives on engagement in the ELL, contextual factors in the educational environment, and perceptions of harmony/discord between ELL and religious beliefs. These findings highlight the complex linguistic dynamics that exist within pesantren settings, emphasizing the need for tailored pedagogical strategies to be formulated and implemented. This discussion emphasizes the necessity for a thorough investigation that takes into account the perspectives of different stakeholders and the specific contexts of institutions to understand the intricacies of the language learning process in the distinct setting of pesantren. This research project has the potential to make a significant contribution towards the development of culturally sensitive and inclusive language learning environments.